Central retinal artery occlusion in an ANCA negative Churg-Strauss syndrome patient - Türkçüo?lu, Peykan; Isik, Ahmet; Deniz, Nurettin; Turgut, Burak; Kan, Elif Kiliç (My University, 2007)
Purpose: To describe a central retinal artery occlusion in a patient with antineutrophil cytoplasmic antibody (ANCA) negative Churg-Strauss syndrome. Methods: Review of clinical and laboratory findings of a 44-year-old woman with ANCA negative Churg-Strauss syndrome that developed sudden vision loss in left eye. Results: Left central retinal artery occlusion was diagnosed by retinal whitening, a cherry-red spot, and delayed arterial filling on fluorescein angiography. Perinuclear ANCA and cytoplasmic ANCA were negative. Conclusion: Central retinal artery occlusion can occur in ANCA negative Churg-Strauss syndrome. Patients with this diagnosis should be considered for prophylactic high dose corticosteroid, regardless of their ANCA status. © Springer Science+Business Media, Inc. 2007.
Keywords: ANCA; Central retinal artery occlusion; Churg-Strauss syndrome